Neck Motion and Injuries of Small Females and Midsize Males in Frontal Impacts at Two Severities - Corina Espelien; John-Paul Donlon; Jeesoo Shin; Mary Gallaher; Sara Sochor; Junior Noss; Randolff Carpenter; Pablo Gracia Cemborain; Jason Forman (Annals of Biomedical Engineering, 2026)
Purpose Head and neck injuries remain a critical area of concern in automotive safety. To inform injury prediction tools, like crash test dummies, neck validation data are needed. While neck response information for midsize males is available, anthropometry-specific data are needed for other body shapes, including small females. The objective of this study is to characterize the neck response (head and neck kinematics and neck injuries) for small females and compare it to the response of midsize males in the same testing conditions. Methods Six small adult female post-mortem human subjects (PMHS) and three midsize adult male PMHS were each tested twice, once at 3-g (20 km/h) and again at 8-g (43 km/h) in frontal impacts. Motion-capture measurements of the skull and first thoracic vertebrae (T1) were analyzed to calculate head and neck motion. Results Females had less downward and less forward head excursion than males for both 3-g and 8-g impact tests. The decreases in peak head responses between the 8-g and 3-g tests were larger for small females than for males, with the largest decrease of 30% for small female downward excursion. Rotation responses were similar for females and males at 3-g. At 8-g; the overall range of T1 pitch was similar for both sexes, although males exhibited an initial rearward T1 pitch. No injuries were found for the male PMHS, while two of the female PMHS had cervical spine injuries. Conclusion These kinematic and injury data can be used for injury prediction tool neck validation.

Disc Injury and Spine Loads in Low-to-Moderate-Severity Frontal Impacts - Richard Kent; Jason Forman (Annals of Biomedical Engineering, 2025)
Purpose Determine the cervical and lumbar spine forces and moments generated in belted occupants in frontal impacts up to 40-km/h change in velocity ( $${Δ }V$$ Δ V ) and assess their potential to cause spinal disc injury. Methods Loads experienced by anthropomorphic test devices, human volunteers, and human cadavers were measured in 282 impact tests. Functions were developed to describe the expected loads as functions of $${Δ }V$$ Δ V for small females, mid-size males, and large males. Loads were contextualized by comparison to injury assessment reference values, manual lifting standards, the compressive loads that have caused spinal disc injuries in vitro, and the compressive spinal loads that occur in other situations. Results The functions confirm that the spinal loads are well below any established injury assessment reference value. Compressive loads are within the range of loads voluntarily tolerated during daily activities and well below the loads that have caused disc injuries in biomechanical studies. Conclusion This study confirms the lack of a biomechanical foundation to assert specific causation when a belted occupant presents with isolated disc herniations, bulges, or extrusions through the annulus following a frontal impact under 40-km/h $${Δ }V$$ Δ V .

Correction to: Disc Injury and Spine Loads in Low-to-Moderate-Severity Frontal Impacts - Richard Kent; Jason Forman (Annals of Biomedical Engineering, 2025)

The Effects of Recline Angle and Restraint Geometry on Lap Belt–Pelvis Interaction for Above-Normal BMI Motor Vehicle Occupants - Rachel Richardson; John-Paul Donlon; Bronislaw Gepner; Jason Forman; Jason Hallman; Jason Kerrigan (Annals of Biomedical Engineering, 2023)

Development of an Injury Risk Function for the Anterior Pelvis Under Frontal Lap Belt Loading Conditions - David Moreau; Pavel Chernyavskiy; Sara Sochor; Bronislaw Gepner; Jason Forman; Martin Östling; Jason R. Kerrigan (Annals of Biomedical Engineering, 2023)

Human Lumbar Spine Injury Risk in Dynamic Combined Compression and Flexion Loading - Sophia K. Tushak; Bronislaw D. Gepner; Jason L. Forman; Jason J. Hallman; Bengt Pipkorn; Jason R. Kerrigan (Annals of Biomedical Engineering, 2023)

Quantifying the Effect of Sex and Neuroanatomical Biomechanical Features on Brain Deformation Response in Finite Element Brain Models - Kristen A. Reynier; J. Sebastian Giudice; Pavel Chernyavskiy; Jason L. Forman; Matthew B. Panzer (Annals of Biomedical Engineering, 2022)

Occupant Restraint in Far-Side Impacts: Cadaveric and WorldSID Responses to a Far-Side Airbag - Daniel Perez-Rapela; John-Paul Donlon; Jason L. Forman; Bengt Pipkorn; Benjamin K. Shurtz; Craig Markusic; Jeff R. Crandall (Annals of Biomedical Engineering, 2021)

Surface Contact Features, Impact Obliquity, and Preimpact Rotational Motion in Concussive Helmet-to-Ground Impacts: Assessment via a New Impact Test Device - Richard Kent; Jason Forman; Ann Bailey; Joseph Cormier; Gwansik Park; Jeff Crandall; Kristy B. Arbogast; Barry Myers (Annals of Biomedical Engineering, 2020)